The Transformation of Planning and Forecasting in Management Accounting: a Bibliometric Analysis of Global Literature from 1973 to 2025 - Rani Julia Pratiwi; Sari Ayu Imaniyah; Puji Handayani; Nurika Restuningdiah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to map the evolution of literature related to planning and forecasting within the context of accounting management using a bibliometric approach. Employing a Systematic Literature Review (SLR) and bibliometric analysis based on data retrieved from the Scopus database between 1973 and 2025, the research identifies trends, knowledge structures, and both established and emerging themes in the field. A total of 55 relevant documents were analyzed using VOSviewer software through co-occurrence analysis, density visualization, and overlay visualization techniques. The findings reveal two major categories in the literature: well-established themes such as "management", "system", and "planning", and emerging topics including "management accounting course", "sustainability", and "reporting practice". These results suggest a shift in research focus toward sustainability integration, digital transformation, and innovation in accounting education curricula. This study contributes both theoretically and practically to the development of more adaptive, data-driven management accounting systems and provides valuable insights for advancing business and management education curricula.